2012
DOI: 10.3164/jcbn.11-22.
|View full text |Cite
|
Sign up to set email alerts
|

The effect of irradiation wavelengths and the crystal structures of titanium dioxide on the formation of singlet oxygen for bacterial killing

Abstract: Safe and effective methods for oral bacterial disinfection have been desired, since bacteria cause many infectious diseases such as dental caries, periodontal disease, and endodontic infections. Singlet oxygen (1O2) is attractive, because it is toxic to prokaryotic cells, but not to eukaryotic cells. We selected irradiation of titanium dioxide (TiO2) as a source of 1O2, because it has been used in sunscreens and cosmetic products without complications. In order to establish the optimal oral photodynamic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…This dye molecule, which was stimulated by light, transfers electrons to the conduction band of semiconductor (TiO 2 ) and then reacts with oxygen molecule on the TiO 2 surface to generate superoxide anion and hydroxyl radicals [18]. Unfortunately, in our study, we could not measure the amount of superoxide anion, partly due to the lower amount of TiO 2 compared with previous studies [17,19]. Moreover, the suitable light for stimulating TiO 2 to generate free radicals, especially superoxide anions, is not visible by UV light [20].…”
Section: Discussioncontrasting
confidence: 50%
“…This dye molecule, which was stimulated by light, transfers electrons to the conduction band of semiconductor (TiO 2 ) and then reacts with oxygen molecule on the TiO 2 surface to generate superoxide anion and hydroxyl radicals [18]. Unfortunately, in our study, we could not measure the amount of superoxide anion, partly due to the lower amount of TiO 2 compared with previous studies [17,19]. Moreover, the suitable light for stimulating TiO 2 to generate free radicals, especially superoxide anions, is not visible by UV light [20].…”
Section: Discussioncontrasting
confidence: 50%
“…Also besides, recent studies have reported the promotion of osseointegration by applying the ROS generated in a photofunctionalization reaction to remove carbon accumulated in TiO 2 formed on the surface of the implant body by ultraviolet (UV) irradiation (17,18) . cal, which is the most oxidative ROS, was generated directly from irradiated rutile -TiO 2 , it was also confirmed that a -PDT via rutile -TiO 2 could be safely applied to dental treatment (19) .…”
Section: Introductionmentioning
confidence: 55%
“…Its photocatalysis is able to promote the peroxidation of the polyunsaturated phospholipid component of the microbial lipid membrane, induce loss of respiratory activity, and elicit cell death. While with those organisms implicated in oral infections, including A. nucleatum, growth inhibitory and killing concentrations under anaerobic conditions are in the same order at 0.25-2.5 and >2.5 mg/mL, respectively (51).…”
Section: Titanium Dioxide (Tio2)mentioning
confidence: 88%
“…It has two structures, the anatase and rutile (51). It is widely used in a number of applications as a powder and increasingly in a nanoparticulate form, and is generally considered to be non-toxic at the concentrations normally employed.…”
Section: Titanium Dioxide (Tio2)mentioning
confidence: 99%